Climate Change Trends and Vulnerabilities in Bangladesh’s Crop Sector: A Review of Crop Production Challenges and Resilience Strategies - Md. Mejbah Uddin; Md. Aminul Hoque (Turkish Journal of Agriculture: Food Science and Technology)
Climate change has become one of the most important threats to worldwide agricultural production systems. This paper evaluates how Bangladesh, a prominent developing country in the low-lying Ganges-Brahmaputra-Meghna delta, is susceptible to climate change and assesses present agricultural practices that target sustaining production under these threats. The study synthesizes the ongoing research findings of climatic change tendency, involving the rising of temperature, alteration of precipitation pattern, along with the onward frequency of extreme weather incidence and their complication to crop production. It discusses the key susceptibilities of Bangladesh’s crop sector, such as a shortage of irrigation water, the impact of rising temperatures, increasing sea levels and the loss of biodiversity. Moreover, the study explores the resilience strategies and measures adopted by farmers, policymakers and researchers to alleviate the hostile effect of climate change on crop production. With all these considerations, the paper aimed to analyse the current climate change trend, adverse effects to agricultural sectors and existing resilience practices in Bangladesh as well as future strategies against climate change.